18(2w-7)=6(6w+10)

Simple and best practice solution for 18(2w-7)=6(6w+10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18(2w-7)=6(6w+10) equation:


Simplifying
18(2w + -7) = 6(6w + 10)

Reorder the terms:
18(-7 + 2w) = 6(6w + 10)
(-7 * 18 + 2w * 18) = 6(6w + 10)
(-126 + 36w) = 6(6w + 10)

Reorder the terms:
-126 + 36w = 6(10 + 6w)
-126 + 36w = (10 * 6 + 6w * 6)
-126 + 36w = (60 + 36w)

Add '-36w' to each side of the equation.
-126 + 36w + -36w = 60 + 36w + -36w

Combine like terms: 36w + -36w = 0
-126 + 0 = 60 + 36w + -36w
-126 = 60 + 36w + -36w

Combine like terms: 36w + -36w = 0
-126 = 60 + 0
-126 = 60

Solving
-126 = 60

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| sin(5x)=cos(x) | | -6z+36=(3z-8) | | (-16/5)/(-12/25) | | 6x+3=-9-6x | | F(5x)=x^2-5 | | -14=-2/3y | | 2x+16y=144 | | 0=T^(3/4)-2T^(1/4) | | 666= | | e^9=6.9 | | 7x=6x+39 | | 5w+11=86 | | y^2+25=169 | | .5n=-65 | | x-2/5=-1/2 | | 2x^6=7x^5 | | (2x-1)/(x^2-2x-3)=(x)/(x^2-9) | | x^2=4a^2 | | 0=(T^(3/4)-2T^(1/4))/4T | | 25a^3+20a^2=0 | | 1/x4 | | -(7y+1)-(-6y-2)=1 | | 8x+12-7x=-9 | | log(4-2)*(3)=36 | | log(x-2)*(3)=36 | | (14x-7y)/7y | | 14x-7x/7y | | L=2w+3a | | 19a^2/952 | | 19a2/95a | | 21-7=20 | | ln(x-2)-ln(x+3)=ln(x+1)-ln(x+6) |

Equations solver categories